Optimalisasi Kegiatan Pembenihan Secara Alami Melalui Pengamatan Fekunditas, Fertilization Rate, Hatching Rate dan Survival Rate Ikan Karper (Cyprinus carpio) - Septihandoko, Kukuh; Mukti, Moch Aziz Arindya; Nindarwi, Daruti Dinda (Nekton, 2021)
Carper fish (Cyprinus carpio) is a freshwater fishery commodity that is currently experiencing rapid development from time to time. The increasingly rapid development and quality cannot be separated from the role of hatchery activities. Therefore, an appropriate program is needed in an effort to improve the quality of carp fish seeds. This study was conducted to evaluate the optimization of the carper fish (Cyprinus carpio) breeding process in order to produce more optimal seeds by studying the natural breeding method. The working method in this study uses a descriptive method with primary and secondary data collection techniques. Parameters observed were fecundity, Fertilization Rate, Hatching Rate, and Survival Rate. The results of the study showed a fecundity value of 240.000 eggs with an FR value of 80%, HR value of 95%, and SR value of 36%.